1990
DOI: 10.1038/bjc.1990.47
|View full text |Cite
|
Sign up to set email alerts
|

31P-NMR spectroscopy and histological studies of the response of rat mammary tumours to endocrine therapy

Abstract: Summary We have shown by 3'P-NMR spectroscopy that ovariectomy, in N-methyl-N-nitrosourea induced mammary adenocarcinomas, increases signals from phosphocreatine (PCr) relative to nucleoside triphosphate (NTP) before measurable regression (2 days) and for at least a further 13 days. The present study correlates the NMR changes with histological changes in the regressing tumour. Mammary tumours were examined by NMR before, and 2 and 14 days after, ovariectomy or sham-ovariectomy. Sections were taken from five t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Figure 3 demonstrates the histological appearance of control tumours and tumours obtained from rats treated with 2.5 μg kg −1 EB1089 for 28 days. The majority of tumours induced by NMU are classified as adenocarcinomas, based upon cytological abnormalities and growth pattern exhibiting a papillary pattern with many mitoses (Stubbs et al , 1990; Mackay et al , 1996). In contrast, sections of tumours from animals treated with EB1089 showed marked loss of cellularity (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 demonstrates the histological appearance of control tumours and tumours obtained from rats treated with 2.5 μg kg −1 EB1089 for 28 days. The majority of tumours induced by NMU are classified as adenocarcinomas, based upon cytological abnormalities and growth pattern exhibiting a papillary pattern with many mitoses (Stubbs et al , 1990; Mackay et al , 1996). In contrast, sections of tumours from animals treated with EB1089 showed marked loss of cellularity (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, or in addition to this mechanism, the tumour blood supply might be improved either directly by tamoxifen itself or as a consequence of reduced oestrogen concentration. We have shown, in the case of ovariectomy, that the MRS changes at 48 h precede any alteration in the cell population (Stubbs et al, 1990). It is likely that this would be true for other endocrine treatments such as 4-hydroxyandrostenedione (Griffiths et al, 1987) and tamoxifen (this paper).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Vaupel et al (1987) found that small human mammary carcinoma xenografts grown in nude rats have a higher oxygen consumption than that of normal post-menopausal human breast and that both oxygen consumption and tumour blood flow decreased as the tumours increased in size. On the other hand, when a tumour responds to chemotherapy (Ng et al, 1982;Steen et al, 1988), radiotherapy (Evanochko et al, 1983;Tozer et al, 1989) or endocrine therapy (Griffiths et al, 1987;Rodrigues et al, 1988;Stubbs et al, 1990) the opposite effect is usually observed -the ratios of high energy phosphates (PCr and NTP) relative to Pi decrease, sometimes before any detectable change in the volume is recorded (Rodrigues et al, 1988) and before there are any detectable histological changes (Stubbs et al, 1990). Steen (1989) has reviewed reports of such paradoxical improvements in the ratio of high energy phosphates to Pi in experimental tumours after various forms of therapy, which he terms 'metabolic activation'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations